Comparative modeling and molecular refinement of the enzyme Phosphoglucosamine mutase from Mycobacterium tuberculosis - Costa, Jhonatan; Pereira, Wildrimak; Barros, Romulo; Mendes, Diego; Cardoso Júnior, Fábio; Ramos, Ricardo (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS); 2019: Anais da VII Escola Regional de Computação Aplicada à Saúde, 2019)
Tuberculosis (TB) is the leading cause of death from an infectious agent in the world according to the World Health Organization (WHO) and the epidemic is being strengthened by the emergence of Multi and eXtensively Drug Resistant strains (MDR-TB and XDR-TB), decreasing the treatment options that have been used for decades. The GlmM catalyzes the interconversion of glucosamine-6-phosphate (GlcN6P) to glucosamine-1-phosphate (GlcN1P), catalyzing the second step of the biosynthesis process of UDPGlcNAc (uridine diphospho-N-acetylglucosamine) which is essential for the life cycle of Mycobacterium Tuberculosis (MTB). In the present study, comparative modeling and molecular refinement techniques were used to generate a three-dimensional model of MTB GlmM enzyme.